Colombia - Decentralization : Options and Incentives for Efficiency - Sector Annexes - World Bank (World Bank, 2012)
This report is intended to support the analysis and implementation of reforms aimed at a strengthening of the intergovernmental system in Colombia. In mid-2007 congress approved a legislative act as constitutional amendment that increases the level of the main transfer to sub-national governments, the General System of Transfers (SGP). However an adjustment of the regulations and institutional arrangements within the sectors is still pending. The report is intended to provide empirical evidence and technical inputs for a design of these complementary measures that are required. It will focus on examining how efficient sub-national governments are in service delivery within the existing intergovernmental arrangements and incentive framework. It will also analyze the underlying causes of low performance and suggest options for the government to address this challenge. The emphasis is on three sectors: education and health, which are both financed primarily by the SGP; and the road sector, which is financed outside the SGP. This focus will make evident the different types of intergovernmental management systems and the implications for efficiency.